Platelet Lysate Nusantara (PL-NUSA) Product Packaging Design Using The Nigel Cross Approach - Radita Dwi Putera; Alfandi Setya Pradana; Katon Muhammad; Akhlis Rahman Sari Nurhidayat (Engineering Faculty, UNSOED, 2025)
The health industry is currently developing rapidly. One of the products that is currently developing is Platelet Lysate. Platelet Lysate is an alternative medium for cell growth. In industry, the makers of Platelet Lysate produce quite a lot of waste. Therefore, the waste is reprocessed into a new product called Platelet Lysate Nusantara (PL-Nusa) to reduce waste. Because PL-Nusa is reprocessed waste, something is needed to increase the value of the product. One way is to make packaging. Packaging is not only to increase the value of the product but also as a protective tool so that the product is protected from infection. To make packaging, packaging design needs to be carried out to suit the desires and needs of consumers. In the PL-Nusa product, the design was carried out using the Nigel Cross approach. The results obtained are that the packaging used for PL-Nusa is 100ml with a circular, serrated, and rotated lid. While the packaging shape is in the form of a tube with the same size from top to bottom. And the material used for packaging uses PP (Polypropylene).